MiRNA-Seq reveals key MicroRNAs involved in fat metabolism of sheep liver - Fei, Xiaojuan; Jin, Meilin; Yuan, Zehu; Li, Taotao; Lu, Zengkui; Wang, Huihua; Lu, Jian; Quan, Kai; Yang, Junxiang; He, Maochang; Wang, Tingpu; Wang, Yuqin; et al. (Frontiers in Genetics, 2023)
There is a genetic difference between Hu sheep (short/fat-tailed sheep) and Tibetan sheep (short/thin-tailed sheep) in tail type, because of fat metabolism. Previous studies have mainly focused directly on sheep tail fat, which is not the main organ of fat metabolism. The function of miRNAs in sheep liver fat metabolism has not been thoroughly elucidated. In this study, miRNA-Seq was used to identify miRNAs in the liver tissue of three Hu sheep (short/fat-tailed sheep) and three Tibetan sheep (short/thin-tailed sheep) to characterize the differences in fat metabolism of sheep. In our study, Hu sheep was in a control group, we identified 11 differentially expressed miRNAs (DE miRNAs), including six up-regulated miRNAs and five down-regulated miRNAs. Miranda and RNAhybrid were used to predict the target genes of DE miRNAs, obtaining 3,404 target genes. A total of 115 and 67 GO terms as well as 54 and 5 KEGG pathways were significantly (padj < 0.05) enriched for predicted 3,109 target genes of up-regulated and 295 target genes of down-regulated miRNAs, respectively. oar-miR-432 was one of the most up-regulated miRNAs between Hu sheep and Tibetan sheep. And SIRT1 is one of the potential target genes of oar-miR-432. Furthermore, functional validation using the dual-luciferase reporter assay indicated that the up-regulated miRNA; oar-miR-432 potentially targeted sirtuin 1 (SIRT1) expression. Then, the oar-miR-432 mimic transfected into preadipocytes resulted in inhibited expression of SIRT1. This is the first time reported that the expression of SIRT1 gene was regulated by oar-miR-432 in fat metabolism of sheep liver. These results could provide a meaningful theoretical basis for studying the fat metabolism of sheep.